(untitled) (Acta Polytechnica CTU Proceedings, 2018)
Currently, the extensive research in the field of cutting ceramics is conducted and there are efforts to replace cemented carbides by these materials. However, the problem is to improve the production of ideal compact samples. Therefore, the influence of mechanical machining technologies on the values of macroscopic residual stresses was investigated by X-ray diffraction. The resulting values were discussed depending on machining parameters and surface structure of the studied samples.